Legal Analysis of Cryptocurency Utilization in Indonesia - Wira Agustian Tri Haryanto; Muhammad Irayadi; Andri Wahyudi (Yayasan Adra Karima Hubbi, 2023)
Background. Bitcoin is the world's first digital currency that uses the concept of Cryptocurrency, which is a digital asset designed as a medium of exchange using cryptographic techniques to secure transactions and control the administration of its currency units that are likely to continue to grow in the future. Based on Law No. 7 of 2011 on Currency or cryptocurrencies, Bitcoin cannot be considered as legal tender in Indonesia. Purpose. It is said to be a means of payment because the means of payment in Indonesia is the Rupiah, but based on the Regulation of the Minister of Trade of the Republic of Indonesia Number 99 of 2019, crypto assets are one of the commodities that can be used as the subject of futures contracts traded on futures exchanges. Method. his research uses a statute approach. In addition, a case approach is also used to find out the ratio decidendi used by the Constitutional Court judges in deciding cases of judicial review of laws related to indigenous peoples. Results. This type of research is normative juridical research. The nature of research in this research is descriptive analytical. The type of data used in this research is library research. The validity of crypto asset transactions based on Indonesian contract law which refers to the Civil Code is valid because it fulfills the terms of the agreement in article 1320 of the Civil Code and is supported by the principles contained in the Civil Code itself, including the principle of freedom of contract, the principle of consensualism, the principle of pacta sunt servanda, and the principle of good faith. Therefore, crypto asset transactions are also legalized according to Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE) because crypto asset transactions are carried out online through the internet network. Conclusion. The Indonesian government then compiled several rules to accommodate interests as guidelines and clarity for the public regarding the government's recognition of the existence of bitcoin and virtual currencies, namely through the policy of the Minister of Trade of the Republic of Indonesia Number 99 of 2019, and based on the rules of the Bappebti Regulation Number 5 of 2019 concerning Technical Provisions for the Implementation of the Crypto Asset Physical Market on the Futures Exchange.